MANAJEMEN PEMBIAYAAN PENDIDIKAN PONDOK PESANTREN TAHFIDZUL QUR’AN - Wasik Nur Mahmudah; Mukhibat (Excelencia: Journal of Islamic Education & Management, 2021)
Education financing management is very influential on competency development. With good financing management, the competency development of students in the institution will also be good. This study aims to explain how the management of Tahfidzul Qur'an education funding at the Hamalatul Qur'an Islamic Boarding School, Jogoroto Jombang. This type of research in qualitative research is a case study. Meanwhile, for data analysis in this study using the theory of Miles and Huberman: reduction, data presentation and drawing conclusions. Based on the data collection and analysis process, the researcher can conclude that the management of education financing at the Hamalatul Qur'an Jogoroto Islamic Boarding School, Jombang, is carried out using conventional methods. Funding is done using the cash waqf model and service waqf which is carried out through direct fundraising and indirect fundraising. In financial management (accommodation, investment, and personnel) caregivers have a very high accountability, so that they are able to generate a high sense of credibility to donors. The activities carried out were very efficient and effective, which was marked by the students being free of all costs, both direct and indirect costs, but the students were able to memorize 30 juz of Al-Qur'an within 6 months which was in accordance with the requirements of the hafidz quarantine program. It can be concluded that even though an educational institution carries out conventional education funding, it is not necessarily that the institution is unable to develop the existing competencies of students / students.